PERANCANGAN KONSEP IDEAL DESA WISATA DI DESA CIBINUANG KABUPATEN KUNINGAN - Rahajaan, Jerry Dounald; Kurniadi, Erik; Yusuf, Fahmi; Darmawan, Erlan; Herawati, Resma Mega (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2020)
Cibinuang Village is an area located in Kuningan District, Kuningan Regency. Cibinuang Village has many and varied natural resources. In the process of development activities Cibinuang tourism village has not fully used the detailed concept of tourism. The development of the concept of tourism in the Village of Cibinuang did not escape the existence of adequate natural resources and quality human resources. The availability of natural resources and their use in Cibinuang Village, even if simple and limited, will be able to improve the quality of the village and be a source of increased human resources for the community. In terms of improving the economy, knowledge and attractiveness of tourism. Efforts to design the concept of a tourist village, in improving the ability of rural communities in the field of tourism required a whole design concept to make it happen. It is understood together that one of the concrete manifestations of Higher Education gait besides education and research is Community Service and Service activities, this is in accordance with what is mandated in Law No. 20 of 2003 concerning National Education System article 24 (2) which states;